La oración de Infinitivo en latín: una visión crítica - Castro Delgado, Gilberto (2012)
We propose an analysis of the Accusative with Infinitive construction (AcI) as a prototypical structure of complementation, arguing mostly the presence of an accusative case and an infinitive mode that form a complete structure with an extensive productivity among the authors in the classical and literary latin.